The Group Involutory Matrix of the Combinations of Two Idempotent Matrices - Lingling Wu; Xiaoji Liu; Yaoming Yu (Journal of Applied Mathematics)
We discuss the following problem: when aP+bQ+cPQ+dQP+ePQP+fQPQ+gPQPQ of idempotent matrices P and Q, where a,b,c,d,e,f,g∈ℂ and a≠0, b≠0, is group involutory.